1974
DOI: 10.1111/j.1432-1033.1974.tb03817.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inhibitors of Protein Synthesis on Cholesterol Side‐Chain Cleavage in the Mitochondria of Luteinized Rat Ovaries

Abstract: Conversion of cholesterol to pregnenolone, termed cholesterol side‐chain cleavage, has been studied in isolated mitochondria from luteinized rat ovaries. Cholesterol in these mitochondria in the presence of cyanoketone is converted to one product pregnenolone on addition of a suitable electron donor. The percentage conversion of total mitochondrial cholesterol to pregnenolone is comparable to that measured by the percentage conversion of [4‐14C]cholesterol to [4‐14C]pregnenolone when the label has been preincu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…As noted above, this step is considered rate-limiting because hydrophobic cholesterol cannot rapidly diffuse through the aqueous intermembrane space of the mitochondria to support acute steroid synthesis and requires the participation of a de novo synthesized labile protein [61][62][63][64][65]. The search for the putative regulatory protein identified several candidate proteins, namely SCP2, DBI, SAP, peripheral benzodiazepine receptor (PBR), steroidogenesis inducing protein (SIP), and steroidogenic acute regulatory protein (StAR) [58].…”
Section: Hormonal Regulation Of Steroidogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, this step is considered rate-limiting because hydrophobic cholesterol cannot rapidly diffuse through the aqueous intermembrane space of the mitochondria to support acute steroid synthesis and requires the participation of a de novo synthesized labile protein [61][62][63][64][65]. The search for the putative regulatory protein identified several candidate proteins, namely SCP2, DBI, SAP, peripheral benzodiazepine receptor (PBR), steroidogenesis inducing protein (SIP), and steroidogenic acute regulatory protein (StAR) [58].…”
Section: Hormonal Regulation Of Steroidogenesismentioning
confidence: 99%
“…When supplied with freely diffusible cholesterol analog (i.e., hydroxyl cholesterols), adrenocortical and testicular Leydig cells from aging rats are totally competent in producing steroids (corticosterone and testosterone). The "acute" production of steroids is dependent upon a hormone-stimulated, rapidly synthesized, cyclohexamide-sensitive and highly labile protein whose function is to transfer cholesterol from outer to inner mitochondrial membranes [53,[61][62][63]. StarD1/StAR is now identified as a putative acute regulatory protein [53,58,59,76,90,417,418].…”
Section: Aging and P38 Subfamily Of Map Kinasesmentioning
confidence: 99%
“…The rate-limiting step in steroidogenesis is thought to be the side-chain cleavage of cholesterol to produce pregnenolone [28], and the importance of a rapidly turning over protein in this reaction has been demonstrated [20,29,30]. Work in our laboratory has shown that the rate-limiting step in the cleavage of the cholesterol side chain is the supply of cholesterol to the mitochondria1 cholesterol side chain cleavage mixed-function oxidase enzyme [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Work in our laboratory has shown that the rate-limiting step in the cleavage of the cholesterol side chain is the supply of cholesterol to the mitochondria1 cholesterol side chain cleavage mixed-function oxidase enzyme [29,30]. If mitochondrial cholesterol is being consumed for pregnenolone production it is quite possible that in the cell the major adrenal reservoir of cholesterol esters, the lipid droplets, in conjunction with cholesterol ester hydrolase play an important role in supplying the substrate, cholesterol, to the mitochondria for pregnenolone production induced by adrenocorticotropin.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the cholesterol side-chain cleavage enzyme is of particular interest because the rate of pregnenolone synthesis by this enzyme appears to limit the rate of steroidogenesis in ovarian follicles and corpora lutea (Dorrington, 1977). The major pool of cytochrome P-450 in the corpus luteum is mitochondrial (Stevenson & Taylor, 1971; Arthur & Boyd, 1974) and shows characteristics of the cytochrome P-450 that is involved in cholesterol side-chain cleavage (Jefcoate, Simpson & Boyd, 1974). The cytochrome P-450 component of the cholesterol side-chain cleavage enzyme was measured because it takes part in the binding of cholesterol, a step thought to be regulated by LH (Dorrington, 1977).…”
Section: Introductionmentioning
confidence: 99%